Tautos atminties vaizdai: vizualinis XX amžiaus Lietuvos istorijos stereotipizavimas Lietuvos dokumentikoje - Šermukšnytė, Rūta (Lietuvos istorijos studijos, 2005)
The article aims to answer the following questions: what are the reasons for the stereotyped vision of the Lithuanian history? What views have become conventional representations of certain historical events, phenomena, and processes in Lithuania? A series of documentary films on the Lithuanian history of the 20th century created in 1990-2004 has been chosen as the object of the analysis. The analysis has shown that manifestations of stereotyped visions of the Lithuanian history are determined by certain cinematographic tendencies. Historical films and programs that are considered to be an adaptation of the national narrative cinematography have been predominant since the Lithuanian independence in 1991. This kind of narration is characterized by the validation of history as a national value, formation of national identity, and its stabilization rather than diversification and correction of the historical memory or the development of critical thinking. The current documentary material that is based on the understanding of history as a myth of the nation’s history is not aimed at creating a new visual and verbal narration about the realities of the past, but rather at recognizing what has been said and made in the previous works. The repetition of the visions is also related to visual material as illustration rather than a perception of it as a historical source of a certain fact. Due to such thinking of creators of documentary films, they are not very ardent in seeking new material for films in foreign archives of view and sound. Also, Lithuanian history sometimes is being represented by pictures taken from facts that are not originally Lithuanian. Besides, sometimes a real meaning of views is being hidden under an additional comment behind the picture. Such tendencies have been observed in representing the most important historical events and processes for the Lithuanian statehood of the 20th century - namely, the occupation of Vilnius and Klaipeda, the restitution of Vilnius, the annexation of Lithuania by the Soviet Union, collectivization, the National Revival Movement "Atgimimas" of 1991, and finally, the events of January 13th.